2021
DOI: 10.1183/13993003.00972-2021
|View full text |Cite
|
Sign up to set email alerts
|

The novel bronchodilator navafenterol: a phase 2a, multicentre, randomised, double-blind, placebo-controlled crossover trial in COPD

Abstract: BackgroundNavafenterol (AZD8871) belongs to a new class of bronchodilator, the single-molecule muscarinic antagonist and beta agonist (MABA), being developed for the treatment of chronic obstructive pulmonary disease (COPD). This study aimed to evaluate the efficacy, pharmacokinetics and safety of navafenterol versus placebo and an active comparator treatment for moderate-to-severe COPD.MethodsThis phase 2a, randomised, multicentre (Germany and UK), double-blind, double-dummy, three-way complete crossover stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Navafenterol or AZD8871/LAS191351 at a dose of 400 ​μg caused significant and sustained bronchodilation that was superior to that induced by placebo, and at a dose of 1800 ​μg was more effective than 150 ​μg indacaterol or 18 ​μg tiotropium, without eliciting the occurrence of adverse events ( Singh et al., 2020a ). Furthermore, at a dose of 600 ​μg once daily it provoked FEV 1 changes in patients with COPD similar to those observed with umeclidinium/vilanterol 62.5/25 ​μg once daily ( Singh et al., 2021 ). CHF6366 is another interesting MABA.…”
Section: Evolution In Pulmonary Drug Delivery Devicessupporting
confidence: 62%
“…Navafenterol or AZD8871/LAS191351 at a dose of 400 ​μg caused significant and sustained bronchodilation that was superior to that induced by placebo, and at a dose of 1800 ​μg was more effective than 150 ​μg indacaterol or 18 ​μg tiotropium, without eliciting the occurrence of adverse events ( Singh et al., 2020a ). Furthermore, at a dose of 600 ​μg once daily it provoked FEV 1 changes in patients with COPD similar to those observed with umeclidinium/vilanterol 62.5/25 ​μg once daily ( Singh et al., 2021 ). CHF6366 is another interesting MABA.…”
Section: Evolution In Pulmonary Drug Delivery Devicessupporting
confidence: 62%
“…Although there were small significant changes in lung function in the BD group, health status was unaffected 51 . By contrast, combining long‐acting beta‐agonist and anti‐muscarinic properties in a single molecule is now possible and the novel compound navafenterol proved to be at least as effective as the dual BD combinations in reducing symptoms and improving lung function 52 …”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…A phase II study has demonstrated lung function improvements compared with placebo with an acceptable tolerability profile in patients treated with inhaled batefenterol plus fluticasone once daily [ 78 ]. Navafenterol (AZD8871) is a MABA that has undergone a phase IIa three-way crossover study that compared 2 weeks’ treatment with inhaled navafenterol, inhaled umeclidinium plus vilanterol, and placebo [ 79 ]. Navafenterol was well tolerated and demonstrated significant improvements in trough FEV 1 versus placebo (mean difference 0.202 L; p < 0.0001); no significant difference versus umeclidinium plus vilanterol was observed [ 79 ].…”
Section: Non-cholinergic Targets For Copd Treatmentmentioning
confidence: 99%
“…Navafenterol (AZD8871) is a MABA that has undergone a phase IIa three-way crossover study that compared 2 weeks’ treatment with inhaled navafenterol, inhaled umeclidinium plus vilanterol, and placebo [ 79 ]. Navafenterol was well tolerated and demonstrated significant improvements in trough FEV 1 versus placebo (mean difference 0.202 L; p < 0.0001); no significant difference versus umeclidinium plus vilanterol was observed [ 79 ]. It is currently unclear if clinical development of batefenterol or navafenterol will proceed further.…”
Section: Non-cholinergic Targets For Copd Treatmentmentioning
confidence: 99%